Novel Approach in NIR Photodetectors: Integrating Plasmonic Upconversion Composite Film With ITZO Transistor - La, Ju A.; Jang, Ho Seong; Kim, Jaekyun; Kang, JoonHyun; Kang, Taewook; Kang, Gumin; Ko, Hyungduk (Institute of Electrical and Electronics Engineers, 2024)
Metal oxide semiconductors are of great interest for enabling near-infrared photodetectors (NIR PDs) due to their advantages, such as high optical transparency, reduced leakage current, and high electron mobility. However, these metal oxide semiconductors are insufficient to excite an electron into a conduction band under NIR light, usually because they have a large electronic bandgap (corresponding to the ultraviolet wavelength). Here, we report a novel NIR photodetection method using metal oxide semiconductor-based PDs by integrating a plasmonic upconversion composite tape onto an indium-tin-zinc oxide (ITZO) transistor. We discover that attaching a superboosted hierarchical plasmonic upconversion (HPU) tape to the ITZO layer significantly enhances optical absorption at 1550 nm, the excitation wavelength of upconversion nanoparticles (UCNPs). We demonstrate that the proposed HPU/ITZO transistor achieves the photoresponsive characteristics, including a responsivity and detectivity of approximately 0.49 A W(-1 )and 1.81x 10(12) Jones, respectively, under a light intensity of 0.5 mW cm(-2). Furthermore, we show that a 20x 20 transistor array, composed of the proposed NIR PDs, achieves an NIR light mapping image at the attached region of the HPU tape. We believe that our strategy provides great potential for fabricating NIR imaging sensor systems utilizing metal oxide semiconductors.